CONTESTING ISLAMIC SPIRIT AND ISLAMIC FORMALIZATION: GUS DUR PERSPECTIVES - Khasanah, Faizatun (Teosofia: Indonesian Journal of Islamic Mysticism, 2020)
In today’s context, Islamic values seem to be allied from Moslem’s life, but the symbol of formal Islam looks always presented in many representations, as well as the people of politic and economic’ world are always using Islamic symbols to direct public opinion. The reason is probably due to religious symbol becomes one of the most effective determinants in this regard. These actual facts are contradicted with the idea of Islam formulated by Gus Dur. He has proposed the idea of Islamic Spirit. That’s why? I would like to propose two questions: what is the contextual meaning of Gus Dur's thoughts about Islamic Spirit, and what if the idea is juxtaposed to the emergence of extreme Islamic thought. For this sake, I use critical-analysis method. The result has shown that the context of Gus Dur’s thought was the emergence of the idea of formalizing Islamic Sharia into the constitutions of the state, Indonesia, after the fall of Soeharto’s new order. Then, Gus Dur tried to countering these new ideologies of Islamic formalization. Islam, based on Gus Dur perspective, is encouraging people to be performing any good deed. To be a good Muslim, someone has no need to do good deed in the name of Islam, but he could be enough having a humanism visions. Therefore, there is no need to formalizing Islam